The Jamaica-Britain border and drug trafficking - Haughton, Suzette A. (2007)
Analyzes the basis for a Jamaica-Britain border and examines the problems affecting this border. Demonstrates that Jamaican-British agreements have proven beneficial in curbing border problems across the Jamaica-Britain border region.